Level of Satisfaction and Quality of Life of Caregivers of People with Disabilities in Secondary Dental Care - Graziane Ribeiro Couto; Emílio Prado Fonseca; Regiane Cristina do Amaral (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess the level of satisfaction and quality of life (QOL) of caregivers of Patients with Special Needs seen at the Dental Specialties Center in Aracaju, Brazil. Material and Methods: The Program for Primary Care Access and Quality Improvement (PMAQ - DSC) and the World Health Organization's Quality of Life - Brief (WHOQOL-BREF) questionnaires were applied to PSN and caregivers. Results: The PMAQ questionnaire was applied to 31 patients or caregivers; 97% had no paid work and 61% used public transportation to reach the Dental Specialties Center. The WHOQOL-BREF questionnaire was applied to 20 caregivers; 60% considered their life to be good; however, 60% had practically no leisure time. Correlation tests (Pearson's coefficient) showed a statistically significant correlation between the physical and psychological domain (p=0.02; r=0.64), the psychological and social domain (p=0.033; r=0.48), and the psychological and environment domain (p<0.001; r=0.80). Conclusion: The caregivers and patients with special needs felt satisfied with the specialized oral health service offered by the municipality. Concerning the quality of life of caregivers, the majority stated they had a good quality of life, despite not having the opportunity to participate in leisure-oriented activities and often having negative feelings.